2022
DOI: 10.1371/journal.pone.0262720
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors for tuberculosis among people living with HIV in Nepal

Abstract: Background Worldwide tuberculosis (TB) takes more lives than any other infectious diseases. WHO estimates around 68,000 incident TB cases in Nepal. However, in 2018 only around 27,232 new TB cases were reported in the national system, resulting around 40,768 incident TB cases missing every year in Nepal. National Tuberculosis Control Center carried out this study in anti-retroviral therapy (ART) sites to estimate the prevalence of TB and identify the associated risk factors for TB among the people living with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
(29 reference statements)
1
14
1
Order By: Relevance
“…Our study revealed both similarities and differences in economic and other factors influencing practitioners' STI POCT use, perceived barriers to test adoption, priorities for test development, and desired test characteristics longitudinally and between participants from HICs versus LMICs. This study extends results from a similar clinician survey conducted by our group in 2009, in which >89% of participants were from the US, Canada or Europe 9,11 and adds to the limited literature on practitioner preferences for STI POCT 7 by enabling comparisons between HICs and LMICs over time.…”
Section: Discussionsupporting
confidence: 73%
“…Our study revealed both similarities and differences in economic and other factors influencing practitioners' STI POCT use, perceived barriers to test adoption, priorities for test development, and desired test characteristics longitudinally and between participants from HICs versus LMICs. This study extends results from a similar clinician survey conducted by our group in 2009, in which >89% of participants were from the US, Canada or Europe 9,11 and adds to the limited literature on practitioner preferences for STI POCT 7 by enabling comparisons between HICs and LMICs over time.…”
Section: Discussionsupporting
confidence: 73%
“…However, various studies conducted in other countries have shown that migrant population and ethnic minorities have higher prevalence of TB in comparison to general population [49][50][51][52][53]. This could be because of interactions between cultural and structural barriers to accessing healthcare [3,4,[50][51][52][53][54]. Behind this, social power and structures have influenced vulnerability and treatment outcome of TB among people living in slums and densely populated urban settings, people living in congregate settings like factories, prisons, camps and refugees [44].…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not identify significant differences in TB related outcomes across ethnic groups. However, various studies conducted in other countries have shown that migrant population and ethnic minorities have higher prevalence of TB in comparison to general population [49][50][51][52][53]. This could be because of interactions between cultural and structural barriers to accessing healthcare [3,4,[50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…WHO clinical stages III and IV are indicators of advanced HIV disease and likely a compromised immune status [ 37 ]. As such, individuals who present in these stages often possess cell of differentiation (CD4) count of less than 200 cells/μL, making them substantially vulnerable to developing TB disease [ 38 ] regardless of IPT status. Perhaps, findings by Golub et al substantiate this suggestion [ 39 ].…”
Section: Discussionmentioning
confidence: 99%